Infestation of Spodoptera frugiperda on corn in Bengkulu at different elevations - Ginting, Sempurna; Chozin, Mohammad; Sudjatmiko, Sigit (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Pest infestation is a significant challenge in corn cultivation due to the potential damage it can cause, leading to reduced crop productivity or even complete crop failure. This study aims to assess the infestation of Spodoptera frugiperda on corn in Bengkulu, considering various elevations. Ten hybrids resulting from crosses between promising lines (Caps 2 x Caps 17A, Caps 3 x Caps 17A, Caps 3 x Caps 17B, Caps 5 x Caps 22, Caps 5 x Caps 17B, Caps 15 x Caps 22, Caps 17B x Caps 23, Caps 17A x Caps 17B, Caps 17A x Caps 22, Caps 22 x Caps 23) and three commercial hybrid varieties (Bonanza, Paragon, and Secada) were evaluated across three locations at different elevations: lowland (30 meters above sea level) (masl), midland (600 masl), and highland (1000 masl). The assessment focused on the extent of damage and the plant’s resistance to S. frugiperda infestations. The infestation of S. frugiperda is higher at an elevation of 30 masl compared to locations at 600 masl and 1000 masl. Scoring leaf damage caused by S. frugiperda infestation at 30 masl: 2.73–4.86, at 600 masl: 2.73–3.55, and at 1000 masl: 2.4–3.37.